INVESTIGATION AND MICROPROPAGATION OF BIOACTIVE COMPOUNDS IN SEMI-AQUATIC PLANT POTHOS TENER WALL. AS FISH ANTIMICROBE - Sri Windyaswari, Ari
Araceae family plants are globally distributed and possess a high degree of diversity. The genus Pothos, belonging to the Araceae family, is extensively utilized in traditional medicine in Asia. The Pothos genus includes some well-known species, such as Pothos scandens and Pothos chinensis, which hold significance in traditional Chinese medicine and play a crucial role in Indian ayurveda. However, the species P. tener Wall, a plant native to Sulawesi, has not been thoroughly studied for human and animal uses. According to reports, the P. tener plant exhibits potential as a natural antibacterial for freshwater fish. Additionally, the study aims to explore invitro conservation methods, such as micropropagation, to prevent the extinction of P. tener if it is utilized in the pharmaceutical sector. It is important to note that P. tener is a plant species native to restricted habitats. The initial phase of the research was to identify newly harvested P. tener plants to verify the accuracy of the materials being used. Afterward, the raw materials underwent a comprehensive standardization process encompassing both particular and non-specific criteria for crude drug and extracts. The morphological investigations indicate that P. tener possesses pinnate spines, with leaves that exhibit an ovate, elliptical, or lanceolate shape with a pointed apex. The microscopic analysis reveals the presence of ambibraxiparacytic stomata, rosette crystal distribution, and osmophore secretory cells, distinctive features commonly found in the Araceae family. The plant samples were sequentially extracted using the cold maceration method with nhexane, ethyl acetate, and methanol as solvents. The metabolite profiles of n-hexane, ethyl acetate, and methanol extracts of P. tener were analyzed using GC-MS. The GC-MS analysis revealed a 213 compounds in the three P. tener extracts, with 73 compounds in the n-hexane extract, 114 compounds in the ethyl acetate extract, and 26 compounds in the methanol extract. The total compound content identified in the three P. tener extracts included phthalic acid esters (81.63%). The total compound content in the methanol and ethyl acetate extracts includes fatty acids (19.56%). The total compound content in the methanol and n-hexane extracts includes fatty acid methyl esters (27.93%). The total compound content in n-hexane and ethyl acetate extracts includes alkanes (18.03%). Another compound detected in the methanol extract was alcohol (6.69%). Other compounds detected in ethyl acetate were phenol (3.06%) and aldehyde (1.82%). Meanwhile stigmasterol (2.31%) was detected in n-hexane extract.These compounds are present in all three extracts of P. tener. Phytochemical screening of the three P. tener extracts revealed the existence of alkaloids, tannins, polyphenols, flavonoids, quinones, mono/sesquiterpenes, steroids, and triterpenoids. In the study’s second phase, the aim was to separate active compounds from P. tener, guided by the outcomes of antibiotic activity testing. The research commenced by conducting a mapping of the antibacterial activity of three P. tener extracts against various test microorganisms, namely Staphylococcus aureus ATCC 6538, Aeromonas hydrophila ATCC 7966, Eschericia coli ATCC 8939, Aspergillus niger ATCC 16404, and Candida albicans ATCC 10231. The test technique employed to ascertain the Minimum Inhibitory Concentration (MIC) value involves a microdilution test method, followed by a streak plate method to obtain the Minimum Bactericidal Concentration (MBC) value for all test microorganisms. Furthermore, an agar diffusion test was conducted on the test fungus A. niger and C. albicans to ascertain the precise diameter of the inhibitory zone. The test findings indicated that the methanol extract exhibited the high activity level against all tested microorganisms compared to the other extracts. The MIC and MBC values of the methanol extract in the concentration range of 1.97 µg/mL to 2000 µg/mL reported for S. aureus, A. hydrophila, E. coli respectively were 250 and 500 µg/mL (moderate), while for A. niger and C. albicans in the concentration range of 12,207 µg/mL to 25,000 µg/mL was 195.31 µg/mL (moderate). The methanol extract showed an inhibitory zone with a diameter of 15.36 ± 0.23 mm against A. niger and 9.73 ± 0.11 mm against C. albicans. A specific extract has been chosen for further separation. Following the antimicrobial activity test, the selected extract is the methanol extract of P. tener. The chosen sample was subsequently separated using vacuum liquid chromatography (VLC). The VLC eluent system used was gradient elution (n-hexane 100%, n-hexane-ethyl acetate (8:2), n-hexane-ethyl acetate (5:5 ), n-hexaneethyl acetate (3:7), 100% methanol) resulting in 7 combined fractions.. Based on the VLC results, seven fractions were found when combined. Based on the TLC monitoring pattern, the seven fractions were consolidated into three combined fractions (F1-F3) before being tested for antibacterial activity against A. hydrophila and A. niger. The MIC and MBC values for fractions F1, F2, and F3 against A. hydrophila were as follows: F1-MIC: 976.56 µg/ml (weak), MBC: 1953.12 µg/mL (inactive); F2-MIC: 97.65 µg/ml (strong potential), MBC: 195.31 µg/mL (moderate potential); F3-MIC: 976.56 µg/mL (weak potential). The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values for fractions F1, F2, and F3 against A. niger are as follows: F1 is inactive at a concentration of 1000 µg/ml for both MIC and MBC; F2 is inactive at a concentration of 2000 µg/ml for both MIC and MBC; F3 is moderate potential at a concentration of 250 µg/ml for MIC and inactive at a concentration of 1000 µg/ml for MBC, with an MBC value less than 2000 µg/ml. Following the antimicrobial activity test, the chosen fraction (F2) underwent subfractionation using VLC, once. The VLC eluent system used was gradient elution (n-hexane-ethyl acetate (9.5:0.5), n-hexane-ethyl acetate (9:1), 100% methanol) resulting in 9 fractions. Based on the TLC monitoring, the 9 fractions were combined to obtain 5 subfractions (SF 2.1-SF 2.5). According to the TLC monitoring pattern, SF 2.3 and 2.4 were combined to create SF A. The initial separation involved the SF A fraction, which was subjected to KCV once. This process resulted in 17 subfractions, which were subsequently merged into seven subfractions labeled SF A.1 to SF A.7. After the recrystallization process, one fraction of SF A.4 formed crystals, so that the SF A.4 crystals were continued to the purification stage. The first purification was carried out on the SF A.4 crystals using crystallization techniques to produce 3 parts, namely the n-hexane soluble part (SF A.4.1), partially soluble n-hexane (SF A.4.2) and white crystals that did not dissolve n-hexane (SF A.4.3). TLC monitoring was carried out on the three parts, then the pure compound obtained from SF A.4.3 was tested for its purity. The purity test of SF A.4.3 with 1-dimensional TLC using three different polarity movement phases, 2-dimensional TLC and melting point test. The isolate from SF A.4.3 was given a code until the pure compound PT-01 (39.2 mg) was obtained which was continued to the isolate characterization stage. The second separation was carried out on the SF A subfraction using radial chromatography to produce 6 combined subfractions (SF A.1.2-SF A.1.6). Then, SF A.1.2 and SF A.1.5 were combined into SF X based on the TLC monitoring pattern. The second purification was carried out on the SF X subfraction using flash column chromatography (FC) to obtain 5 subfractions (SSF X.1-SSF X.5). Based on the chromatogram results, the pure compound SFF X.2 coded PT-02 was tested for purity using the same purification method as the SF A.4.3 isolate. The pure isolate PT-02 (9.1 mg) was continued to the isolate characterization stage. The third separation was carried out on the SF 2.2 subfraction (350 mg) using flash column chromatography (FC) to obtain 4 subfractions (SSF 2.2.1-2.2.4). The final purification was carried out on the pure compound that fluoresces blue under UV366nm light on SSF 2.2.4 (36.4 mg). The SSF 2.1.4 subfraction was tested for purity. The pure isolate from SF 2.1.4 was given the code PT-03 (68.1 mg) and continued to the isolate characterization stage. The three isolates (PT-01, PT-02, and PT-03) were subsequently subjected to antimicrobial activity testing utilizing the microdilution method and streak plate. The MIC values of isolates PT01, PT-02 and PT-03 in the concentration range of 1.97 µg/mL to 2000 µg/mL against A. hydrophila were respectively 500 µg/mL (moderate potency); 2000 µg/mL (inactive), 2000 µg/mL (inactive). The MBC values of isolates PT-01, PT-02 and PT-03 in the concentration range of 1.97 µg/mL to 2000 µg/mL against A. hydrophila were respectively 500 µg/mL (moderate potency), >2000 µg/ mL (inactive) and 2000 µg/mL (inactive). The MBC values of isolates PT-01, PT-02 and PT-03 against A. niger were respectively 500 µg/mL (moderate potency); 500 µg/mL (moderate potency) and 1000 µg/mL (weak potency). The MBC values of isolates PT-01, PT-02 and PT-03 against A. niger were respectively 500 µg/mL (moderate potency); 1000 µg/mL (moderate potency) and 1000 µg/mL (weak potency). According to the findings of the antimicrobial activity test, it has been determined that PT-01 is the compound that exhibits activity, whilst PT-02 and PT-03 are compounds used as markers. The structural properties of isolates PT-01, PT-02, and PT-03 were analyzed using Ultraviolet (UV) spectroscopy, Fourier-transform Infrared Spectroscopy (FT-IR), Mass Spectroscopy (MS), and Nuclear Magnetic Resonance (NMR). Through the structural analysis, it was determined that isolate P-01 included stigmasterol, isolate PT-02 had bis-2 (ethylhexyl) pphthalate or Di-2 (ethylhexyl) pphthalate (DEHP), and isolate PT-03 contained dibutyl pphthalate (DBP). This study presents the discovery of PT-01, which is the initial instance of stigmasterol being effectively extracted from P. tener. In addition, the DEHP and DBP were the initial marker compounds extracted from P. tener. In vitro micropropagation is a technique aimed at augmenting the concentrations of the bioactive chemical stigmasterol, while also serving as a conservation measure to safeguard against extinction. After analyzing the metabolite content profile in Wild Type P. tener, it was found that there was no stigmasterol content in the methanol extract. Therefore, it is necessary to employ tissue culture procedures to enhance stigmasterol levels. The process of in vitro micropropagation was conducted by utilizing agar medium for the growth of plants and adventitious root culture in liquid media. Two different basal media, namely Murashige-Skoog and B5-Gamborg (MS and B5), were employed for this purpose. The basal media were both adjusted by adding macronutrient supplementation, including 0.25x KNO3, organic compounds, and vitamins. The vitamins included myo-inositol (1x), sucrose (1/3x), nicotinic acid (4x), pyridoxine HCl (4x), and thiamin HCl (4x). Additionally, a synthetic cytokinin growth regulator called 6-benzyl-aminopurine (BA) was added at a concentration of 0.1 mg/mL Plant Growth Hormone (PGRs). After observing for 28 days on agar media, it was found that the most suitable medium for micropropagation in the MS group was Supplemented MS (M2), while in the B5 group it was Supplemented B5+0.1BA (B3). These mediums were chosen because they resulted in the production of shoots and segments with optimal branching. Subsequently, adventitious root culture was conducted using optimal plantlets cultivated in two sets of basal media, namely MS and B5. Three 3 cm roots were extracted from 28-day-old plantlets and subsequently cultivated in modified liquid media. Liquid media modification involves the use of nutritional modifications, such as agar media, along with two synthetic auxin growth hormones, Indole Butyric Acid (IBA) and Naphthalene Acetic Acid (NAA). After observing for 28 days on liquid media, it was found that the best medium for adventitious root culture in the MS group was Supplemented MS+IBA (code: MSC) and group B5 Supplemented B5+IBA (code: B5C). These mediums resulted in the most optimal root elongation and number. The acclimation process lasted for a duration of 2 months on M2, B3, MC2, and BC3 shoots due to their successful root growth. The process of planting plantlets was conducted in an aquarium using a mixture of growing media consisting of damp soil, river stones, and 250 mL of water. The planting was done at a temperature of 25 oC and lasted for a duration of 8 weeks. After a duration of 4 weeks, introduce a single specimen of the freshwater fish species Betta splendens into the aquarium. During the observation period spanning weeks 1 to 4, the plants derived from the in vitro subculture exhibited continuing growth. Shoots and leaves were formed by in vitro plants cultivated on M2 and B3 medium, whereas fine hairy roots were produced by MC2 and BC2. In addition, between the 4th to 8th week, all plantlets exhibited growth, with the exception of plantlet BC2, which perished in the 7th week. The determination of stigmasterol were determined in the results of optimal subculture on agar media and optimum subculture on liquid media. This analysis was conducted on two groups of MS and B5 media using High Performance Liquid Chromatography (HPLC). The HPLC analysis results indicated that the plantlets grown on agar modified media, specifically Supplemented MS (M2) media, had the greatest levels of stigmasterol at 1.100%. on contrast, the liquid modified media, MS+200 IBA (MSC) media, had stigmasterol levels of 0.47%. The stigmasterol production in wild type P. tener increased from 0.427% to 1.100% in 4-week-old plantlets, however the rise was not initially noticeable. The findings of this study demonstrate the capacity of in vitro tissue culture to produce stigmasterol and contribute to the preservation of P. tener for meeting present and future pharmaceutical demands.